2020
DOI: 10.31729/jnma.4796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of E. Coli in Urinary Tract Infection of Children Aged 1-15 Years in A Medical College of Eastern Nepal

Abstract: Introduction: Urinary tract infection is one of the commonest causes of childhood morbidity. Earlydiagnosis and appropriate choice of antimicrobials is essential. Hence, this study aims to identify theprevalence of Escherichia coli in childhood urinary tract infections. Methods: This was a hospital based descriptive cross-sectional study conducted in Nobel MedicalCollege, Biratnagar over a period of one year. A total of 163 cases aged 1-15 years were included andclinical profile, laboratory reports inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
4
3
0
1
Order By: Relevance
“…Thus, the prevalence in our study was correlated with that of developing countries. In our study, women were more significantly affected than men, and this finding was observed in other studies as well [ 2 , 12 ]. The close proximity of the urethra to the anus is the major predisposing factor, which is responsible for the frequent contamination of urethral passage by fecal flora.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the prevalence in our study was correlated with that of developing countries. In our study, women were more significantly affected than men, and this finding was observed in other studies as well [ 2 , 12 ]. The close proximity of the urethra to the anus is the major predisposing factor, which is responsible for the frequent contamination of urethral passage by fecal flora.…”
Section: Discussionsupporting
confidence: 91%
“…This is comparable to studies by Ullah A and Seifu WD. (6,14) E coli was the commonest bacteria responsible for urinary tract infection in our study comparable to many other studies (12,15,16,17,18,19) followed by Candida species.…”
Section: Discussionsupporting
confidence: 91%
“…Urinary tract infections are common in children [ 1 3 ]. Early diagnosis and treatment are necessary for the prevention of complications [ 4 ].…”
Section: Introductionmentioning
confidence: 99%